2013
DOI: 10.3851/imp2482
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences for Hepatitis B Therapy

Abstract: Patients' preferences are important in evaluating drug selection for CHB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…This study reported that 77.5% of the patients would choose the most effective drug regardless of cost, and most patients preferred oral routes of administration over other therapy regimens. 25 Although there are differences in study designs (eg efficacy was defined by functional cure in our investigation and no costs were included in our study due to the general reimbursement system in Germany), these findings largely align with ours in terms of the general conclusion that long-term efficacy is clearly preferred by patients, and that patients favor tablets as the preferred route of administration.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This study reported that 77.5% of the patients would choose the most effective drug regardless of cost, and most patients preferred oral routes of administration over other therapy regimens. 25 Although there are differences in study designs (eg efficacy was defined by functional cure in our investigation and no costs were included in our study due to the general reimbursement system in Germany), these findings largely align with ours in terms of the general conclusion that long-term efficacy is clearly preferred by patients, and that patients favor tablets as the preferred route of administration.…”
Section: Discussionsupporting
confidence: 80%
“…However, our age distribution (mean age 49.1 years) was in line with another survey of patients with CHB in Singapore, which reported a mean age of 47 years. 25 Several studies investigated patients' and physicians' preferences over treatment alternatives for different hepatitis types. For example, studies focusing on hepatitis C treatments showed a variety of outcomes (sustained viral response, treatment frequency, therapy duration) to be important from the perspective of patients and physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, this strategy of finite ETV therapy is safe and effective if proper off‐therapy monitoring plan offered, and can be considered as a feasible alternative to indefinite Nuc therapy. This strategy is particularly important for low resources countries where cost/reimbursement is a problem and where Nucs with high resistance are still used in substantial number of patients, not only in Asian countries including rich Singapore but also in some European countries such as Poland and Turkey in up to 45% of the patients …”
Section: Discussionmentioning
confidence: 99%
“…The costs of not screening and the consequences of hepatic injury and death outweigh the negligible costs of screening 79 . Screening is probably feasible and acceptable to both patients and healthcare providers because it is a minimally invasive test, and providing screening probably has no effect on health equity 80 . Hepatitis C screening.…”
Section: Infection Screening and Vaccination Recommendationsmentioning
confidence: 99%